Peran Mata Kuliah IT For Business Terhadap Life Skill Mahasiswa - Haq, Dliyaul (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2016)
This research concentrates on IT for Business because it is closely related to contemporary IT skills. The word business also has its own charm because the business needs almost every person. Thus, through this course is expected to know the student response and the cause of their lack of understanding of IT. This research is a field research and is qualitative. The approach used in this research is explorative. To collect data, researchers get it through interviews, observation, and documentation. Associated with data analysis, researchers used descriptive-analytical methods. From the results of research, it is known that IT for business courses give a positive impact to develop and generate courage and skills for students in the field of IT.